Monitorare e valutare il miglioramento scolastico III Seminario "I dati INVALSI: uno strumento per la ricerca" - Falzetti, Patrizia (INVALSI per la Ricerca, 2021)
One of the main goals of the Italian National Evaluation System, since its establishment in 2013, is to strengthen the link between improvement and evaluation. Over the years, after some resistance, schools began to reflect about their activities and organization, having thus the real chance to explore new enhancing paths. This increasing awareness has contributed to broaden studies and educational research. The Seminar "INVALSI data: a research tool" organized for several years by the Statistical Service of INVALSI, gives also to headmasters and teachers (in addition to researchers) the opportunity to show and share ideas, suggestions, best practices, and trials. This is the issue of this book which collects six studies submitted at III edition of the Seminar "INVALSI data: a research and teaching tool" held in Bari from 26th to 28th October 2018. Thanks to INVALSI data, researchers and teachers can strengthen the necessary partnership for educational research and in order to improve students' achievement.